QUALITY IMPROVEMENT DESIGN AT ISLAMIC SCHOOLS POST-COVID-19 PANDEMIC IN ELEMENTARY SCHOOL AND INTEGRATED EARLY CHILDHOOD EDUCATION OF SALEH CHILDREN, MALANG CITY - Muhammad Fahmi Hidayatullah (Universitas Islam Negeri (UIN) Mataram, 2021)
The combination of integrated educational design by integrating general science and religion and the religious character-building education has made the public entrust their sons and daughters to study at the institution. However, the problem is that quality is always a problem, even though the expectation of quality education is a requirement. The Anak Saleh Educational Foundation in Malang City is a consistent institution and committed to quality improvement. Researchers collect data using a descriptive qualitative approach and case study research type with a multi-cases design. Data collection techniques using in-depth interviews, participatory observation, and documentation. The data analysis technique used cross-case data analysis. The results showed connectivity between input, process, and output in improving the quality of Islamic education institutions based on the institution's philosophy, namely Panca Character.